Penurunan Angka Kuman Air Minum Dengan Metode Maserasi Daun Ipomoea carnea - Sri Poerwati (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2021)
Drinking water is a basic necessity of living. It will be a problem if it contains microorganisms. Drinking water Standard based on WHO and the Republic of Indonesia Regulation No. 492 / Menkes / Per / IV / 2010 where microorganisms must be zero and must be processed. The society has not done drinking water treatment either chemically or by other methods. As a natural alternative, Ipomoea carnea contains active ingredients such as alkaloids and flavonoids which can be used as antibacterial subtances. The study aims to prove the extract of leaves of Ipomoea carnea in reducing the bacteriological content of drinking water source ofs springs. This research is an experimental research in the laboratory and the field. Samples in the from of sources of drinking water from springs that do not quality bacteriological with purposive sampling. Maserasi methods the extract of leaves of Ipomoea carnea with MPN Coliform test with one way anova analysis. The results obtained revealed that The results obtained revealed that consentration 0,15g/100mL samples water drinking source springs extract of leaves of Ipomoea carnea can reduce bacteriological content 80,33%.